Enchant to Resist: Galicians Tales of Enchantment and Female Resistance - Lacombe, Fernanda (Madrygal. Revista de Estudios Gallegos, 2018)
This article deals with an analysis of Galician oral tradition fairy tales and their reading as narratives of feminine resistance within the patriarchal and misogynist society. Like well-known literature, popular tradition tends to reproduce gender prejudice present in society. Based on the background of the work of Silvia Federici in the 15th and 18th centuries, the genre of fairy tales has in its subtext a record of the transformations created by primitive accumulation that enphasized the difference between men and women, especially those that concern the division of labor by gender, the devaluation of domestic work performed by women and the control of the state over bodies and female reproduction. In addition to this, tales of enchantment present in some of their narratives a discourse that questions misogynist common sense, thus being a model of female subversion and resistance.
Keywords: Oral Tradition; Popular Literature; Female; Fairy Tales.